Application of medical care linkage model in the whole process management of surgery in the treatment of redundant prepuce and phimosis in children (医护联动模式在小儿门诊包皮手术管理中的应用) - ZHANG Qing (张庆); CHEN Puxin (陈普新); TAO Yanling (陶艳玲) (Association of Integrative Nursing, 2021)
Objective To investigate the doctor-nurse-linkage mode in the whole process of surgery in the treatment of redundant prepuce and phimosis in children. Methods Totally 120 cases of redundant prepuce and phimosis in children were randomly divided into two groups, with 60 cases in each group. The traditional medical work mode was adopted in the control group, while a doctor-nurse linkage model was used to manage the whole process of surgery. The degree of pain caused by changing dressings and preputial edema were observed. The time of making appointment for surgery, preoperative waiting time and postoperative dressing change waiting time were recorded. The satisfaction of family members, doctors and nurses were evaluated. Results The degree of pain caused by changing dressings was lower in the observation group than that in the control group (P＜0. 05). The incidence of preputial edema in the observation group was lower than that in the control group (P＜0. 05). Patients in the observation group had shorter waiting time for making surgery appointment, surgery and postoperative dressing change than those in the control group(P＜0. 05). The satisfaction of family members, doctors and nurses in the observation group were higher than those in the control group (P＜0. 05). Conclusion The doctor-nurse linkage mode can maximize the core value of professionals, improve work efficiency, reduce the waiting time of patients, and improve the satisfaction of doctors and patients. (目的 探讨医护联动模式在小儿门诊包皮手术全过程管理中的应用效果。方法 120例门诊包皮手术患儿随机分为观察组和对照组, 各60例。对照组采用常规医疗工作模式, 观察组采用医护联动模式进行全程管理。观察2组患儿换药疼痛程度以及包皮水肿情况, 记录2组患儿预约手术排期时间、手术日术前等待时间、术后换药等待时间, 评价患儿家属、医生、护士满意度。结果 观察组换药疼痛程度低于对照组, 差异有统计学意义(P＜0. 05)。观察组术后水肿发生率低于对照组, 差异有统计学意义(P＜0. 05)。观察组预约手术排期时间、手术日术前等待时间、术后换药等待时间均短于对照组, 差异有统计学意义(P＜0. 05)。观察组患儿家属满意度、医生满意度、护士满意度均高于对照组, 差异有统计学意义(P＜0. 05)。结论 医护联动模式有助于发挥专业人员的核心价值, 提高工作效率, 减少患者等待时间, 提高医患满意度。)